Sosialisasi Penjualan Online Facebook Pada Usaha Gula Aren Ibu Israh Desa Bandu Agung Kab.Kaur - Nurzam, Nurzam; Kurniawan, Kimas; Hidayah, Nenden Restu; Herliamida, Evi; Astiana, Cemas (LPPM Universitas Dehasen Bengkulu, 2025)
0This research aims to improve Mrs. Israh's knowledge and skills as well as in utilizing the Facebook platform as an online sales medium. Micro,ismall andiimedium enterprises (MSMEs) such as Ms. Israh's palm sugar business have great potential to grow through digital marketing. However, they are often constrained by a lack of understanding and ability to implement online sales strategies. The method0used in this0research is action research by providing socialization and direct assistance on creating a business Facebook account, managing product content, interacting with customers, and utilizing Facebook features for promotion. The0results0of the socialization showed0a significant increase0in participants' understanding of the benefits and how to use Facebook for online sales. Ms. Israh began to actively create and manage her business Facebook page, upload product photos and descriptions, and interact with potential customers. This activity is expected to expand market reach, increase sales volume, and ultimately empower the economy of palm sugar businesses in Bandu Agung Village.